2017
DOI: 10.1016/j.ophtha.2017.06.027
|View full text |Cite|
|
Sign up to set email alerts
|

Sustained Benefits of Ranibizumab with or without Laser in Branch Retinal Vein Occlusion

Abstract: The BRIGHTER study results confirmed the long-term efficacy and safety profile of PRN dosing driven by individualized VA stabilization criteria using ranibizumab 0.5 mg in patients with BRVO. Addition of laser did not lead to better functional outcomes or lower treatment need. The safety results were consistent with the well-established safety profile of ranibizumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
104
3
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(118 citation statements)
references
References 14 publications
9
104
3
2
Order By: Relevance
“…In the RETAIN study, which examined the long-term outcomes after IVR injection in eyes with a BRVO, the final visual acuity was not significantly different between the eyes with resolved macular oedema and eyes with unresolved macular oedema after 4 years 8. In addition, the BRIGHTER study reported that the presence of macular ischaemia did not affect the BCVA outcome after 2 years 9. It was found that the anti-VEGF therapy for macular oedema is effective and can decrease the damages of the photoreceptors 27–29.…”
Section: Discussionmentioning
confidence: 99%
“…In the RETAIN study, which examined the long-term outcomes after IVR injection in eyes with a BRVO, the final visual acuity was not significantly different between the eyes with resolved macular oedema and eyes with unresolved macular oedema after 4 years 8. In addition, the BRIGHTER study reported that the presence of macular ischaemia did not affect the BCVA outcome after 2 years 9. It was found that the anti-VEGF therapy for macular oedema is effective and can decrease the damages of the photoreceptors 27–29.…”
Section: Discussionmentioning
confidence: 99%
“…; Tadayoni et al. ), early treatment with VEGF inhibitors resulted in better treatment outcome than deferred treatment. Thus, early initiation of treatment with VEGF inhibitors should probably be a preference when treating MO induced by BRVO.…”
Section: Discussionmentioning
confidence: 98%
“…Scatter photocoagulation has been added in the treatment of RVO to reduce the burden of intravitreal anti-VEGF injections due to retinal ischemia and the high VEGF levels. However, some studies including the RELATE study revealed that adding laser did not result in the better visual and anatomical outcomes or reduce the need for frequent anti-VEGF injections [49][50][51]. In terms of the treatment regimen, the anti-VEGF therapy was frequently initiated with monthly scheduled injections for six doses, and then the monthly asneeded regimen was usually applied to maintain an optimum level of visual function and macular thickness.…”
Section: Expert Commentarymentioning
confidence: 99%